Ferroptosis: A potential opportunity for intervention of pre-metastatic niche - Zhuo, Shenghua; Yang, Liangwang; Chen, Shenbo; Tang, Caiying; Li, Weicheng; Gao, Zhenzhong; Feng, Jigao; Yang, Kun (Frontiers in Oncology, 2022)
It is widely thought that the tumor microenvironment (TME) provides the “soil” for malignant tumors to survive. Prior to metastasis, the interaction at the host site between factors secreted by primary tumors, bone-marrow-derived cells, with stromal components initiates and establishes a pre-metastatic niche (PMN) characterized by immunosuppression, inflammation, angiogenesis and vascular permeability, as well as lymphangiogenesis, reprogramming and organotropism. Ferroptosis is a non-apoptotic cell death characterized by iron-dependent lipid peroxidation and metabolic constraints. Ferroptotic cancer cells release various signal molecules into the TME to either suppress or promote tumor progression. This review highlights the important role played by ferroptosis in PMN, focusing on the relationship between ferroptosis and PMN characteristics, and discusses future research directions.